Konsep Demokrasi (Syura): Studi Komparatif Menurut Tafsir Al Mishbah dan Tafsir Ibnu Katsir - AlHafidz, Muhammad; Ainur Rha’in (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research discusses a comparison of the concept of democracy in Islam, especially the principle of shura, according to Quraish Shihab and Ibnu Katsir. The two mufassir have different views regarding shura as a democratic principle. Quraish Shihab views shura (deliberation) as a principle that is in line with modern democratic values, such as freedom, equality and justice, using a contextual approach to apply deliberation in the socio-political life of Muslims. On the other hand, Ibn Kathir emphasized the importance of shura, but still based on God's law. He does not link shura directly to modern democracy, but instead views shura as worship and good deeds. This research uses thematic and comparative exegetical methods to examine various verses of the Koran related to deliberation. with the results showing that although the two mufassir have different points of view, they agree that deliberation is an important basic principle in social and state life in Islam. It is hoped that the results of this research will enrich the study of the relationship between shura and democracy and provide an understanding of the relevance of deliberation in contemporary societal life.